ALEXANDRA DELIU, Identity here and there. Migration as resource for identity construction, Print-House Pro Universitaria, Bucharest, 2019 - Dumitru, Cornelia (Calitatea Vieții, 2022)
Migration is a phenomenon, widely researched by social sciences from different angles. However, this book is not about this phenomenon, but is rather a pragmatic, objective and at the same time subjective introspection of the discourses and narratives of migration, and of how these ‘stories’ shift, in turn, the social definitions. The book proposes a constructivist approach in considering migration and identity as two related concepts and how identities are constructed and, we suggest, reconciled with the realities of rural communities. It basically brings a new subjective perspective and knowledge about assimilation and transnationalism, and relates to issues that are documented at theoretical and pragmatic level, albeit from the individuals’ perspective on integration and dealing with political, social or even psychological borders. The volume draws attention and contributes to new knowledge about the shared issues of migrants and stayers alike, leaving open the promise of return migration, while each migrant is faced with new relations and social environments, as well as with new social categories, representing the sometimes looked for or cautiously approached ‘otherness’.